Childcare Use and Its Role in Indigenous Child Development: Evidence from the Longitudinal Study of Indigenous Children in Australia - Zubrick, S; Perales, F; Kalb, G; Chigavazira, A; Farrant, Brad M; Azpitarte, F (My University, 2018)
We investigate patterns of childcare use and its influence on the cognitive development of Indigenous children. The influence of childcare on Indigenous children's cognitive outcomes is less well understood than for non‐Indigenous children due to a lack of appropriate data. We focus on a cohort of Indigenous children in Australia who have been followed from infancy and for whom rich information on childcare use and cognitive outcomes is observed. Compared to Indigenous children who never participated in childcare, Indigenous children who participated in childcare performed better on several early cognitive outcomes. Using regression and propensity score matching, we show that this difference is driven by selection into childcare, with children from more advantaged families being more likely to attend formal childcare. However, matching analysis results suggest that relatively disadvantaged children might benefit more from attending childcare, as indicated by the positive estimated effects found for those who never attended childcare.
Economic Record
Keywords: Child Care; Child Development -- Cognitive; Culture -- Indigenous; Childhood and child development; Child Care; Culture; Child Development; Cognitive; Indigenous; Childhood and child development